"La ley general no deroga el privilegio": Resistance and Negotiation in the Queretaro Corregimiento, 1786-1795 - Celaya Nández, Yovana (Jahrbuch für Geschichte Lateinamerikas, 2025)
In the tradition of Hispanic government, the system of consultations and memorials was a resource widely used by authorities to make evident the exceptionalities of their territories and negotiate the implementation of new regulations out of doubt. A practice sanctioned by a jurisdictional and political culture that extended to the Bourbon government model. The article explores the political, regulatory and jurisdictional resources of the community of councilors of the city of Querétaro to defend their privileges in the context of the changes promoted by the Ordenanza de Intendentes. The defense of privilege in the city government is analyzed from the category of resistance that allows the councilors discourse to be read as a resource to build a space for negotiation and exceptionality of their city and therefore of their forms of government.
Keywords: Bourbon Reforms; Political Government; Jurisdiction.